2019
DOI: 10.1002/chir.23048
|View full text |Cite
|
Sign up to set email alerts
|

Whole cell application of Lactobacillus paracasei BD101 to produce enantiomerically pure (S)‐cyclohexyl(phenyl)methanol

Abstract: In this study, a total of 10 bacterial strains were screened for their ability to reduce cyclohexyl(phenyl)methanone 1 to its corresponding alcohol. Among these strains, Lactobacillus paracasei BD101 was found to be the most successful biocatalyst to reduce the ketones to the corresponding alcohols.The reaction conditions were systematically optimized for the reducing agent L paracasei BD101, which showed high enantioselectivity and conversion for the bioreduction. The preparative scale asymmetric reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 51 publications
(78 reference statements)
1
29
0
Order By: Relevance
“…At the end of the experiment using 30‐mmol substrates, it was observed that the conversion was completed after 62 h, but the ee of the product was very low (81%). This could be due to the reduction in the enzyme activity, suggesting substrate toxicity and inhibition as reported previously . Based on this knowledge, the substrate concentration was investigated with slight changes.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…At the end of the experiment using 30‐mmol substrates, it was observed that the conversion was completed after 62 h, but the ee of the product was very low (81%). This could be due to the reduction in the enzyme activity, suggesting substrate toxicity and inhibition as reported previously . Based on this knowledge, the substrate concentration was investigated with slight changes.…”
Section: Resultsmentioning
confidence: 85%
“…This can be explained by the change of the three‐dimensional structure of the enzyme with the change of pH and interaction of the active center of the enzyme with the substrate, especially the S atom on the substrate. In addition, in the biotransformation process, the substrate should be able to pass through the cell membrane; therefore, selectivity could be changed as it would alter the solubility of the substrate by pH change . The highest conversion (82%) with 88% ee was obtained when the pH was at 6.5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The whole cell biocatalytic synthesis has continually emerged as an outstanding method to replace traditional chemical methods in some fields . Few bacterial strains like, Lactobacillus paracasei BD101 were used as whole cell biocatalyst for pure ( S )‐cyclohexyl (phenyl)methanol . Also, Vitale et al used Lactobacillus reuteri DSM 20016 whole cells for the production of ( S )‐rivastigmine.…”
Section: Introductionmentioning
confidence: 99%